Android Application for Children to Learn Basic Solat - Hamzah, Norhasyimah; Abd Halim, Noor Dayana; Hassan, Mohammad Hafiz; Ariffin, Arihasnida (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The existence of mobile learning application has provided an opportunity for Islamic knowledge to be delivered widely. Accordingly, Muslim application developers have been developing Islamic-based applications for learning about hadith, prayer (solat), and Quran recitation, to list a few. The solat is the pillar of worship that helps Muslims to become better people. Therefore, it is the responsibility of parents to teach their children about solat, particularly when the latter reach the early age of seven. This study aims to (i) develop and incorporate a prayer-learning application that has multimedia elements in order to attract young users and (ii) assess the reliability of the application for children. A learning application can serve as a new method for learning about how to perform a solat. In this approach, solat can be taught digitally using a portable platform, including Android. In this study, an android learning application was developed using Waterfall methodology which consists of five phases: idea, analysis, design, development, evaluation, and final product. Adobe Flash Professional CS6 was chosen as a development platform. The application consists of four modules: “Let’s Pray,” “Five Times Prayer,” “Doa’ After a Prayer,” and “Mind Test.â€  To authenticate the application, the researchers collected data from expertise (lecturers) from the Faculty of Technical and Vocational Education and Faculty of Science, Technology, and Human Development. These respondents were selected through targeted sampling. The result concludes that the application is suitable for new learners to learn about performing a solat.